Lathosterol and other Noncholesterol Sterols in Treatment of Hereditary Hypercholesterolemias: 20-Year Experience among School Children and Adolescents - Hyánek, Josef; Pehal, František; Dubská, Ladislava; Miková, Blanka; Martiníková, Vera; Privarová, Jana; Brtnová, Jana; Táborský, Ludek (Journal of Nutritional Therapeutics, 2018)
Aims: This paper presents our 20-year experience with diagnosing heterozygous familial hypercholesterolemia (HFH) and monitoring its diet and drug treatment in 94 children (6-18 years) by means of noncholesterol sterols (NCS), namely lathosterol (Lat) and desmosterol (Des) as cholesterol synthesis precursors, and campesterol (Cam) and sitosterol (Sit) as cholesterol absorption precursors. Patients and Methods: Four groups were included in the study: (1) 64 children with genetically confirmed HFH; (2) 30 children with clinical and laboratory symptoms of HFH where the relevant genetic mutations have not been found; (3) 77 children with alimentary hyperlipidemia (AH), and (4) 84 healthy children as a control group. The followed-up markers were routine lipid profile comprising total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) and triacylglycerides (TAG), complemented by apolipoprotein A1 (ApoA), apolipoprotein B (ApoB), lipoprotein(a) (Lp(a)), low-density lipoprotein receptor (LDL-R), apolipoprotein E (ApoE) polymorphism, and plasma NCS (Lat, Des, Cam and Sit), the latter being established by means of GC/MS. The medical treatment of HFH patients consisted of simvastatin and ezetimibe. Correlations between TC lowering and decrease in Lat and other NCS values during combination treatment were examined in various types of hypercholesterolemia. Results: HFH patients, whether genetically confirmed or not, exhibit a significant decrease in Lat (and in milder concentrations also Des) which correlates directly to the TC lowering during the combination therapy (r = 0.912 for Lat; r = 0.798 for Des; p<0.001). Cam and Sit do not correlate with the TC lowering at all (r = -0.378 for Cam; r = -0.208 for Sit). By contrast, high TC levels in AH patients are not accompanied by significantly elevated Lat levels, and, therefore, caloric restriction cannot result in significant Lat or Des decrease (p<0.001). Lat and Des levels are also high following drug treatment interruption during long vacations or when the drug treatment is neglected. Compensatory elevation of Cam and Sit occurs in 50% of treated children patients after the desirable TC level below 4.8 mmol/l has been achieved and maintained. In our experience, the combination of statin and ezetimibe is the most efficacious therapy to lower TC together with Lat and Des in children with HFH. Conclusions: Inclusion precursors for cholesterol synthesis and absorption in laboratory testing improve differential diagnosis of HFH, and makes monitoring and/or treatment of pediatric patients more precise and convenient.